Akuntabilitas Pengelolaan Dana Desa Di Desa Saba Kecamatan Blahbatuh Kabupaten Gianyar - Putra Kencana, I Putu Gede; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACTo The problem that occurred in Saba Village as a location in this study was the lack of competency and professionalism of existing human resources in managing village funds. This study aims to analyze the accountability of planning, implementation and accountability of Village Funds in Saba Village. This study uses qualitative methods with descriptive methods. The results of this study indicate that village fund management planning has implemented accountable, transparent and participatory principles that are open to the community. Implementation has implemented the principles of transparency, accountability and participation by involving the public in supervision and providing criticism and suggestions. Accountability in reporting and accountability of village funds is carried out in accordance with the mechanism based on the provisions even though there are still negligence from village government officials and the activity management team (TPK). Keywords :transparency, accountability and the principle of value of money